SPINAL EPIDURAL HEMATOMA: A CASE REPORT - Nur Turhan,; Ayşe Dilek,; Metin Karataş, (Archives of Rheumatology, 2002)
Spinal hematoma is a rare entity among the causes that result in a clinical picture of acute spinal cord compression. Spinal hematomas are frequently localized to the epidural space and less frequently to the subdural space. Spinal hematomas are usually caused by trauma, anticoagulant therapy, vascular anomalies and blood dyscrasias. Prognosis of such hematomas has been reported to be favourably good. We reported a case with spinal epidural hematoma. The case was of interest for its possible etiologic factor, prognosis and anatomic localization. This 71 year old man had become scoliotic due to a previous pulmonary operation the hematome has been localized to the epidural space very close to the apex of the scoliotic curve and his functional state after 2 months from the onset was wheelchair level.